Intrusive light quantification methodology in photometries obtained in a goniophotometer - Velásquez Flores, Carlos Andrés; Espín Villacrés, Francisco Vladimir (I+ T+ C- Research, Technology and Science, 2016)
In the present work a methodology has been developed for the evaluation of intrusive light in photometries obtained in goniofotómetros. This methodology can serve the operational laboratories to quantify this parameter and improve the calculation of the combined uncertainty of the measurement. A percentage intrusion light calculation program was performed from the equation defining the luminous intensity, then measurements were taken over a year. Finally, after adjusting for a Gaussian curve, a mean value was established with a standard uncertainty.